CARA BARU MENINGKATKAN KETAHANAN PANGAN DAN MENURUNKAN EMISI GAS RUMAH KACA DI KALIMANTAN TIMUR - Hasrullah, Hasrullah; Wisesa, Harna Rizki; Andani, Indriani; Sagena, Uni W; Aftah, Chairul (BUANA SAINS, 2024)
This research aimed to understand the implementation and impact of the presence Food Management Agency for Greening (BPPUP) in East Kalimantan. This research uses qualitative methods to understand the implementation and impact of the existence of the Greening Food Management Agency (BPPUP) in East Kalimantan Province, allowing researchers to explore the perspectives of the participants in depth.  The data analysis technique uses the Miles and Huberman model through three stages: data reduction, data presentation, and conclusion. The result showed that in 2023, BPPUP carry out various initiatives such as providing technical direction to 65 companies, validating food land proposals for reforestation covering an area of 85.91 hectares, and determining the location and area of the reforestation program with a total of 242.56 hectares.